Treatment of hypertension in athletes: An evidence-based review - Asplund, C. (The Physician and Sportsmedicine, 2010)
Hypertension is the most common cardiovascular condition in adults. It is also very common in athletes. When lifestyle changes fail, medications may be needed for the treatment of hypertension. When choosing a drug for antihypertensive therapy, providers should choose an agent that has favorable effects on blood pressure and minimal detrimental hemodynamic change during exercise. Evidence supports that the medications with the most favorable effects are angiotensin-converting enzyme inhibitors, calcium channel blockers, a-blockers, and cardiac-selective ß-blockers. The effects of diuretics are less desirable, and nonselective ß-blockers should be a last choice for hypertensive patients who are physically active.